Farmland trees and integrated pest management: a review of current knowledge and developing strategies for sustainable systems - Scott‐Brown, Alison S.; Rial‐Lovera, Karen; Giannitsopoulos, Michail L.; Rickson, R. Jane; Staton, Tom; Walters, Keith F. A.; Burgess, Paul J. (Wiley, 2025)
1. Climate change and the withdrawal of several classes of agrochemicals from use are intensifying the challenges faced by food producers in controlling pests in crop systems. Integrated pest management (IPM), which uses a combination of pest control approaches, is therefore a focus in international initiatives to improve the resilience of food production. 2. Integrating the greater use of trees and shrubs on farms within IPM frameworks offers a biodiversity‐positive contribution to crop protection. For example, trees can modulate the prevalence and impacts of agricultural pests and their natural antagonists through direct and indirect interactions. The beneficial impact of farmland trees and shrubs on pest management in arable or grassland fields can be enhanced from an analysis of variables such as tree species and their spatial distribution on farms, insect‐plant dynamics, population behaviours and soil management practices. 3. The aim of this study is to synthesise existing knowledge and to assess the benefits and trade‐offs between farmland trees and IPM strategies, building on gaps in knowledge identified by a stakeholder survey. Through this targeted review, we delineate the future evidence required to define and quantify the advantages that farmland trees offer as an element of IPM strategies. 4. Practical implication. The development of regional biodiversity monitoring tools, which integrate landscape features such as trees, shows promise for shaping national policies to increase the adoption of IPM. There is a demand for user‐friendly on‐farm tools, adaptable to changing crop and pest priorities, that can support the alignment of the management of farm trees with IPM. However, basic and applied biological and ecological research are needed to inform and validate these decision‐support tools and the capability to inform landscape‐scale models.
The initial report compiled to disseminate the stakeholder-elicitationresults and comments to contributing participants is available in the supporting information (Data S1)
Keywords: 3103 Ecology; integrated pest management; trees outside of woodland; farmland trees; native species; natural enemies